Zachowania prospołeczne studentów pracy socjalnej Uniwersytetu Wrocławskiego - Wiktorowicz-Sosnowska, Monika (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2023)
The topic of pro-social behavior and its impact on the development and formation of humanity’s attitudes has been of interest to many researchers in recent decades. Both the concepts that explain altruism as biologically or personality-driven, and the approach that explains that the phenomenon of helping is the result of upbringing are extremely diverse and represent a wide range of current knowledge. The study sought answers to whether individuals, despite their potential resources to do work “for others,” are susceptible to the influence of external factors. The important question, then, is the relationship and the degree to which the external element will affect the assessment of one’s own altruism. Accordingly, it was hypothesized that once the content of pro-social behavior is activated in the respondents by the method of rolling, there will be an increase in self-esteem. In order to verify the questions and hypotheses, a study was conducted in a group of first-year students at the University of Wroclaw, majoring in Social Work. The study surveyed 45 randomly selected students, divided into two groups, checking the altruism measurement using an online survey. The survey used the A-N questionnaire by Jack Sliwak. The questionnaire consisted of two parts, between which the respondents were shown videos with content showing altruistic and neutral behavior, for the control group. After watching the film, the respondents filled out part two of the questionnaire. The research was carried out in December 2020/January 2021. The result of the research did not confirm the assumed hypothesis that activating people through the phenomenon of rolling, will significantly affect the self-assessment of altruism among students. This shows how complex a phenomenon altruism is to study. The degree of difficulty is due to the need to take into account a number of factors that, as a result of the analyses, may be crucial to the conclusions reached.